Increased Ratio of Global O-GlcNAcylation to Tau Phosphorylation at Thr212 Site Is Associated With Better Memory Function in Patients With Type 2 Diabetes - Huang, Rong; Tian, Sai; Han, Jing; Cai, Rongrong; Lin, Hongyan; Guo, Dan; Wang, Jiaqi; Wang, Shaohua (Frontiers in Physiology, 2019)
Objective: Aberrant O-GlcNAc modification has been implicated in type 2 diabetes mellitus (T2DM) and the pathogenesis of neurodegenerative diseases via competition with tau phosphorylation. We aimed to investigate the association between global O-GlcNAcylation, tau phosphorylation levels and mild cognitive impairment (MCI) in the whole blood of patients with T2DM. Methods: Sociodemographic, clinical characteristics and cognitive performances of the enrolled T2DM subjects were extensively assessed. Global O-GlcNAcylation and tau phosphorylation levels in the whole blood were also determined using Western blot. Results: Forty-eight T2DM subjects, including 24 with MCI and 24 with normal cognition, were enrolled in this study. Compared with cognitively normal controls, T2DM with MCI subjects displayed decreased global O-GlcNAcylation level, but increased tau phosphorylation levels (all p<0.05). To reflect the combined effect, the ratios of global O-GlcNAcylation to tau phosphorylation levels, including specific sites, such as Ser396, Ser404, Thr212 and Thr231, were all significantly decreased in MCI subjects (all p<0.05). Further multivariable logistic regression analysis revealed that high glycated hemoglobin A1c was an independent risk factor, whereas increased O-GlcNAc/p-T212 was an independent protective factor for MCI in patients with T2DM (odds ratio [OR]=2.452, 95% confidence interval [CI] 1.061-5.668, p=0.036; OR=0.028, 95%CI 0.002-0.388, p=0.008, respectively). With regard to each cognitive domain, O-GlcNAc/p-T212 was positively correlated with the score of Auditory Verbal Learning Test-delayed recall (r=0.377, p=0.010). Conclusions: Our study suggests that increased ratio of global O-GlcNAcylation to tau phosphorylation at Thr212 site in the whole blood is associated with decreased risk of MCI, especially with better memory function in T2DM subjects. Trial Registration: ChiCTR-OCC-15006060 (www.chictr.org.cn).